Effect of Round Spiked Threshing Cylinder Geometry on the Threshing Performance of Wheat Crop - Tiwari, R K; Chauhan, S. K. (Indian Journal of Hill Farming, 2018)
For wheat crop threshing, threshing cylinder with round spikes gave the maximum output capacity and threshing efficiency which were observed as 369.3 kg/h and 99.87% at tip diameter of 600 mm and spike thickness of 6 mm corresponding to maximum feed rate of 780 kg/h. The wheat straw size for maximum output capacity and maximum threshing efficiency were 22.67 mm at tip diameter of 600 mm and spike thickness of 6 mm corresponding to maximum feed rate (780 kg/h) in case of round spiked threshing cylinder. The maximum broken grain percent values were 0.833% at feed rate (507 kg/h) corresponding to tip diameter of 600 mm and spike thickness of 10 mm for round spiked threshing cylinder. For higher threshing efficiency, fine straw quality and minimum specific power consumption, round spiked threshing cylinder of 600 mm tip diameter and spike thickness of 6 mm gave best performance results with total grain loss within permissible limit. The spike thickness of 6 mm gave minimum broken grain loss with fine straw quality. But from mass manufacturing point of view, tip diameter of 600 mm and 8 mm round spike thickness will be appropriate for manufacturers. It also delivered good output capacity and threshing efficiency and fine straw quality.